Predominant Role of Immunoglobulin G in the Pathogenesis of Splenomegaly in Murine Lupus - Zhang, Qian; Xiang, Liping; Zaman, Muhammad Haidar; Dong, Wenhui; He, Guodan; Deng, Guo-Min (Frontiers in Immunology, 2020)
Systemic lupus erythematosus (SLE) is characterized by high levels of autoantibodies and multiorgan tissue damage. The pathogenesis of splenomegaly in SLE remains unknown. In this study, the role of immunoglobulin G (IgG) generation and deposition in the inflammation of the spleen and associated dysfunction in SLE was investigated. In the lupus mice, we observed the development of spontaneous splenomegaly, and we found that lupus serum IgG is an important pathological factor involved in the initiation of inflammation and further germinal center (GC) and plasma cell formation. We discovered that macrophages of the splenic marginal zone are dispensable for the GC response induced by lupus IgG, but red pulp macrophages are important for GC responses. Furthermore, we found that pathogenic lupus IgG promotes inflammation and GC formation through the macrophage-mediated secretion of TNF-α. Syk inhibitor treatment suppressed the changes in the histopathology of the spleen induced by lupus IgG. This study will contribute to the understanding of the pathogenesis of splenomegaly in lupus and promote the development of an effective therapeutic strategy for SLE.